Chromium- and copper-induced inhibition of photosynthesis in Euglena gracilis analysed on the single-cell level by fluorescence kinetic microscopy - Rocchetta, Iara (2009)
Here, we investigated effects of copper (Cu) and chromium (Cr) toxicity on two contrasting strains of Euglena gracilis, with and without chloroplasts, grown in culture media promoting either phototrophic or heterotrophic growth. This led to insights into Cr/Cu toxicity mechanisms and into the regulation of phototrophic vs heterotrophic metabolism. Our data strongly suggest that in Cu2+ and Cr6+ stressed Euglena photosynthesis is the primary target of damage. In the applied light conditions, this was mainly damage to the photosystem II reaction centre, as shown by single-cell measurements of photochemical fluorescence quenching. Respiration and photosynthetic dark reactions were less sensitive. The malfunctioning photosynthesis enhanced production of reactive oxygen species (mainly superoxide), leading to elevated amounts of carotenoid degradation products. At higher metal concentrations in chloroplast-containing cells, but not white cells, this oxidative stress resulted in increased respiratory oxygen uptake, likely by damage to mitochondria. During growth in nutrient solution promoting heterotrophic metabolism, the cells were able to repair the metal-induced damage to photosynthesis, moderating the inhibition of photochemistry. Growth in medium forcing the cells into photosynthesis increased the investment in photosynthetic pigments. Comparison of the two Euglena strains surprisingly showed that the previously metal-resistant strain lost this resistance during culture. © 2009 New Phytologist.